Integrasi Pendidikan Karakter dalam Pembelajaran Akidah Akhlak - Mulia, Harpan Reski (State Islamic Institute of Madura, 2020)
In recent time, character education is viewed as important thing in education, even it has been applied in all education institutions. In this writing, the approach of integration theory is used to analyze the integration of character education in learning process of study at school, especially the learning process of Akidah Akhlak. It is because akidah akhlak has a big role in teaching the value of Islam to the students. The objective of this research is to know the process of integration of character education in learning process of Akidah Akhlak. This research used descriptive qualitative method by using phenomenological approach, the phenomenology approach used to understand the phenomenon by looking directly how is the integration of character education in learning process of Akidah Akhlak which is being taught by teachers in class rooms of MIN 11 Aceh Tenggara, based on observation, interview and documentation. The result of this research shows that the integration of character education in learning process of Akidah Akhlak is done through the main competence, the objectives of study and the learning method used by akidah akhlak’s teachers.